2021
DOI: 10.1371/journal.pone.0248838
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hypothermia and adherence to World Health Organisation thermal care guidelines among newborns at Moi Teaching and Referral Hospital, Kenya

Abstract: Neonatal hypothermia is a great concern with near epidemic levels globally. In Kenya, its prevalence is as high as 87% with limited local data on the associated factors such as adherence to warm chain guidelines as recommended by the World Health Organisation (WHO) is limited. This study aimed to determine the prevalence of hypothermia and level of adherence to the WHO thermal care guidelines among newborns admitted at Moi Teaching and Referral Hospital (MTRH). It adopted a prospective study design of followin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…Furthermore, neonates who got kangaroo mother care had 62% less chance of dying than those who did not get the care. Even though our study had not considered the type of KMC provided, the finding is analogous to different studies [ 8 , 9 , 26 , 27 ]. Kangaroo care can help to stabilize heart rate, improve oxygen saturation and respiratory rate, improve infant lactation [ 28 ], and have positive effects on neurological, cognitive, emotional, behavioral, and social development in the short and long term [ 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, neonates who got kangaroo mother care had 62% less chance of dying than those who did not get the care. Even though our study had not considered the type of KMC provided, the finding is analogous to different studies [ 8 , 9 , 26 , 27 ]. Kangaroo care can help to stabilize heart rate, improve oxygen saturation and respiratory rate, improve infant lactation [ 28 ], and have positive effects on neurological, cognitive, emotional, behavioral, and social development in the short and long term [ 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of hypothermia in this study was 25.6%, similar to the results in a study in Rwanda which assessed the prevalence and risk factors for neonatal hypothermia on admission into a tertiary neonatal unit (Choi, Urubuto, Dusabimana, Agaba, & Teteli., 2019). Several factors have been used to explain the differences in the prevalence of hypothermia between studies including methodologies, time at temperature measurements and socio-cultural factors (Nyandiko, Kiptoon, & Lubuya, 2021). In this study, axillary temperature measured within 90 minutes post-delivery was used to assess hypothermia post-delivery in a delivery room whose temperature ranged between 25 and 28 o C. The measurement method and the warm environment could explain the low prevalence of hypothermia compared 67.6% reported among neonates within 72 hours of hospitalisation (Ogunlesi, Ogunfowora, & Ogundeyi., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have suggested a number of risk factors associated with hypothermia in neonates, including maternal hypertension, antenatal use of steroids, low maternal temperature, inadequate antenatal care, low birth weight, prematurity, need for resuscitation, nighttime delivery, delivery during cold season, low birth weight, and prematurity [ 1 , 6 , 9 14 ]. Warmer delivery room or resuscitation room temperatures and warm transport to NICU have been found to be protective against neonatal hypothermia [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%